Para além do "sim, senhor": A aliança renovadora nacional (arena) e a ditadura militar na Paraíba (1964-1969) - Sobreira, Dmitri da Silva Bichara (2016)
This dissertation is the result of research carried out to obtain the title of Master by the Graduate Program in History at the Federal University of Paraíba (PPGH-UFPB). We studied the Aliança Renovadora Nacional (Arena), political party created by the military dictatorship established in Brazil in 1964. Through the Institutional Act #2 (AI-2) organizations created in 1945 was extinct and established a system with only two parties: Arena, supporter of the authoritarian regime, and the Movimento Democrático Brasileiro (MDB), opposition party. We aim verticalize the analysis of the Arena performance in Paraíba, focusing on its Regional Directory, in state politics and eventually at the municipal level. Our time frame are the years from 1964 to 1969 in them analyze the performance of the parties in the civil-military coup in Paraíba, the formation of the Arena party Regional Directorate in this state and in the municipalities of Serra Branca and Sousa, seeking to understand the distribution of local oligarchies in two-party system. We examine the electoral performance of the party in the elections held in 1966 and 1968, highlighting the elections of senator and mayor of Campina Grande city, which help us understand the relationship between different internal coalitions that composed it. Finally, we analyze the performance of ARENA in Paraiba elected representatives to state and federal positions, such as power brokers between civil society and the military commanders of the authoritarian regime. Through previously selected documentation, we seek to understand how the various oligarchies distributed in a multi-party system, which despite electoral rivals shared the same political culture, managed to compose a single party, and devise a list of ARENA with the dictatorship, deciphering the reasons for party image creation "Yes, sir."